Modelagem e quantificação da compactação de latossolos cultivados com eucalipto - Silva, Arystides Resende (2006)
The harvest operations and wood transport involves intensive traffic of machines on the soil, which may traffic in a same line several times, or randomly. Besides the passes number, the wood load transported also may affect the soil compaction, when the applied pressures for the machines exceed its bearing support capacity, altering the place where the root system grow and reducing the productivity. Seeking alternatives ways to minimize the traffic impact on the soil structure, it was surmised the possibility of forest residues use to minimize the traffic impact on the soil structure. The objectives of this study were: a) to develop the bearing capacity models for a Red-Yellow Latosol located in the Santa Maria de Itabira region - MG and to determine with the use of these models the effect of the traffic intensity and load of a Forwarder on the soil structure; b) to evaluate the effect of the residues layer in different traffic intensities on the preconsolidation pressure of a Yellow Latosol and of a Red Latosol in the Belo Oriente and São João Evangelista regions, respectively and c) to evaluate the soil physical and mechanical properties in the three studied regions. Undisturbed soil samples were collected to obtaining the bearing capacity models and to evaluate the traffic intensities and loads of a Forwarder on the soil structure and also to evaluate the effect of different residue conditions on the preconsolidation pressure. The undisturbed soil samples were used in the uniaxial compression test. It was also determined the texture, organic matter, soil particles density, soil density, total porosity, field capacity, permanent wilting point and the penetration resistance (RP). For the Santa Maria de Itabira region all the traffic intensities caused soil compaction in the two studied depths being four passes the one that caused larger soil compaction and as the Forwarder load increased the soil compaction also increased. The traffic on the forest residues lessened the soil compaction in the studied soils mainly in the condition of brushwood and bark (GC), being the worst situation the condition the soil without residues (SR), so much in the Belo Oriente region as in the São João Evangelista region. As the traffic intensity increased from two to eight passes, a larger compaction occurred in the studied conditions. The PR determined with the impact penetrometer, was not sensitive to separate the forest residue type.